Ecosystem Science Fair Projects : Using Worms, Leaves, Crickets, and Other Stuff - Walker, Pam and Wood, Elaine (USA Enslow Publishers, 2005)
Contains science projects that concern the relationship between living things and their environment.
Include Illustrations and Index
Keywords: Ecology projects -- Ecology--Experiments